Kompetenzentwicklung und organisationale Veränderung : Eine Ethnographie zu Veranstaltern von Musikevents - Köster, Petra F. (2015)
How does learning happen in the context of project organisations? And how can the organisation of a project develop against this backdrop? The example of two music events shows how competence development can take place beyond change management and personnel policy as a prerequisite for organisational development.